Hydrogenolysis of sorbitol over Ni, Pt and Ru supported on SBA-15 - Banu, M.; Sankaranarayanan, T. M.; Venuvanalingam, P.; Magesh, G.; Sivasanker, S. (Indian Journal of Chemistry. Section A: Inorganic, Physical, Theoretical & Analytical Chemistry, 2017)
Hydrogenolysis of sorbitol (15% aqueous solution) has been carried out in a batch reactor over Ni (6 wt%), Pt (1 wt%) and Ru (1 wt%) supported on SBA-15 and carbon coated SBA-15 (SBA-15(C)). For comparison, the three metals have also been supported on activated carbon (AC). The catalysts are characterized by XRD, N-2 and H-2 adsorption measurements. Addition of Ca(OH)(2) to the reaction mixture increases conversion and selectivity for the dihydroxy compounds, 1,2-propanediol (PD) and ethylene glycol (EG). Based on yield of dihydric alcohols (PD+EG), the performance of the catalysts at 220 degrees C and 60 bar in the presence of Ca(OH)(2) is in the order: Ru-AC similar to Ru-SBA-15(C) > Ru-SBA-15 similar to Ni-SBA-15, the yields being 40, 39, 31 and 29 wt%, respectively.